The added complications of climate change: understanding and managing biodiversity and ecosystems. Issue 9 (1st November 2013) - Staudt, Amanda; Leidner, Allison K; Howard, Jennifer; Brauman, Kate A; Dukes, Jeffrey S; Hansen, Lara J; Paukert, Craig; Sabo, John; Solórzano, Luis A
Abstract : Ecosystems around the world are already threatened by land‐use and land‐cover change, extraction of natural resources, biological disturbances, and pollution. These environmental stressors have been the primary source of ecosystem degradation to date, and climate change is now exacerbating some of their effects. Ecosystems already under stress are likely to have more rapid and acute reactions to climate change; it is therefore useful to understand how multiple stresses will interact, especially as the magnitude of climate change increases. Understanding these interactions could be critically important in the design of climate adaptation strategies, especially because actions taken by other sectors (eg energy, agriculture, transportation) to address climate change may create new ecosystem stresses.